Overconfidence Sebagai Mediator Antara Regret Aversion Bias dan Risk Tolerance Bagi Investor Muda - Sutisna, Entis; Albart, Nicko (Journal of Business and Economics Research (JBE), 2025)
The capital market plays an important role in the economy as well as in determining the level of economic progress of a country. The capital market and investors are an inseparable entity that continues to grow together. The Indonesian capital market has continued to develop, with current investors being dominated by Millennials and Generation Z, accounting for 35% in West Java. The purpose of this study is to carefully analyze the biases that influence investors when making decisions under uncertainty. In this case, the focus is on regret aversion bias, which is affected by psychological factors such as risk tolerance and overconfidence, situating this research within the scope of micro behavioral finance. The research method applied is descriptive quantitative using a survey approach, with a sample of 150 respondents engaged in various investment instruments. The data were then analyzed using PLS-SEM. The findings reveal that regret aversion bias, risk tolerance, and overconfidence significantly influence investment decisions. Furthermore, risk tolerance through overconfidence has a significant effect on investment decisions, and a similar pattern is observed in regret aversion bias, which also significantly affects investment decisions through overconfidence, particularly among young investors in West Java. The practical implication of this study is that investment decisions ultimately remain the right of investors regardless of the biases influencing them. Investors are still able to act rationally in their investment activities and establish clear criteria in the decision-making process.